Effect of ammonia on methane production, methanogenesis pathway, microbial community and reactor performance under mesophilic and thermophilic conditions. (September 2018) - Yang, Ziyi; Wang, Wen; He, Yanfeng; Zhang, Ruihong; Liu, Guangqing
Abstract: The effects of ammonia on methane production, methanogenesis pathway, microbial community, and reactor performance were investigated in this study. More than 20% of methane production loss was observed in mesophilic and thermophilic reactors when the ammonia level exceeded 2 and 5 g NH4 + -N/L, respectively. The volatile fatty acid (VFA) data indicated that acetogenesis and methanogenesis are strongly influenced by ammonia inhibition under the mesophilic condition, while methanogenesis was mainly affected under thermophilic condition. No evident methanogenesis pathway shift was found in the mesophilic reactor, whereas the increase in NH4 + -N concentration to more than 5 g/L led to a clear shift from aceticlastic to complex and flexible pathways, thereby significantly enriching the hydrogenotrophic pathway in the thermophilic reactor. The function and response of the microbial community to ammonia inhibition were consistent despite the difference in population and diversity under mesophilic and thermophilic conditions. Graphical abstract: Image Highlights: The methane production was lower in mesophilic reactor. Acetogenesis and methanogenesis were influenced under mesophilic condition, with methanogenesis affected under thermophilic. High ammonia suppressed aceticlastic and enhanced hydrogenotrophic pathway. The function of different microbial community faced with ammonia inhibition remained consistent.